2019
DOI: 10.3390/catal9050463
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization of a Dye-Decolorizing Peroxidase from Pseudomonas Fluorescens Pf0-1

Abstract: The consumption of dyes is increasing worldwide in line with the increase of population and demand for clothes and other colored products. However, the efficiency of dyeing processes is still poor and results in large amounts of colored effluents. It is desired to develop a portfolio of enzymes which can be used for the treatment of colored wastewaters. Herein, we used genome sequence information to discover a dye-decolorizing peroxidase (DyP) from Pseudomonas fluorescens Pf-01. Two genes putatively encoding f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…It is also noteworthy to investigate if DypB does play a role on lignin degradation. Moreover, a study [69] showed that the dye-decolorizing peroxidase Pf DyP B2 from Pseudomonas fluorescences Pf0-1 can insert carbene into an N-H bond. Investigation of these non-natural reactions can be a nice addition to the enzymatic reactions that these dye-decolorizing peroxidases can do.…”
Section: Discussionmentioning
confidence: 99%
“…It is also noteworthy to investigate if DypB does play a role on lignin degradation. Moreover, a study [69] showed that the dye-decolorizing peroxidase Pf DyP B2 from Pseudomonas fluorescences Pf0-1 can insert carbene into an N-H bond. Investigation of these non-natural reactions can be a nice addition to the enzymatic reactions that these dye-decolorizing peroxidases can do.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme technology possesses great potential to reduce environmental pollution and offers potential benefits in the comprehensive utilization of lignocellulosic biomass. Lignocellulolytic enzymes have received attention because of their potential applications in various agro-industrial bioprocesses, such as the conversion of hemicellulosic biomass to fuels and chemical production, the clarification of juices, the green processing of certain foods and beverages, the enhancement of animal digestibility in feedstock, the delignification of paper and pulp, the improvement of fabric properties in the textile industry and waste utilization [277][278][279]. Cellulase is widely used in the textile and laundry detergent industries as it can play a part in the hydrolysis of cellulose and improve fabric properties for the textile industry and for cleaning textiles in the laundry detergent industry [154,280].…”
Section: Application Of Lignocellulolytic Enzymes In Bioprocessingmentioning
confidence: 99%
“…The food and beverage processing industries have used cellulase for the hydrolysis of cellulose during the drying of coffee beans and for the extraction of fruits and vegetables in juice production [281,282]. Cellulase, α-l-arabinofuranosidases and other glycosidases have also been used in brewery and wine production [213,277]. The enzymatic hydrolysis of grapes utilizes α-l-arabinofuranosidases and other glycosidases to enhance the flavor of wine by the release of free terpenols, an important aspect in the development of the aroma in wine.…”
Section: Application Of Lignocellulolytic Enzymes In Bioprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial DyPs are increasingly being discovered and are the most abundant members of the putative DyP family (PeroxiBase; accessed on 9 March 2021). The continuous advancement in recombinant DNA technology has improved the potential for the successful and cheap production of active recombinant DyPs in Escherichia coli systems [ 29 , 30 , 31 ]. It is interesting to note that, unlike their eukaryotic counterparts, such as SBP and HRP, which are very difficult to produce in active forms using bacterial expression systems, recombinant bacterial and fungal DyPs appear to be reasonably well expressed in E. coli .…”
Section: Introductionmentioning
confidence: 99%